Evaluasi kualitas pelayanan dengan metode airqual, importance-performance analysis dan competitive zone of tolerance-based importance-performance analysis - Syaiful Akmal; Firman Firman (Universitas Negeri Padang, 2020)
This study aims to identify and provide priority proposals for improving the quality of airline services in Indonesia, case studies of X Airline and Y Airline using the AIRQUAL method and the Competitive Zone of Tolerance Based Importance-Performance Analysis (CZIPA). This research is classified as descriptive research. The population in this study are all X Air and Y passengers residing in West Sumatra. The sampling technique in this study is using purposive sampling technique with the criteria of respondents who have been on X or Y Airline at least 3 times and boarded the aircraft in the last 3 years. The total sample is 530 samples. The data used are primary data obtained from online questionnaires. Data analysis method used is the Competitive Zone of Tolerance Based Importance-Performance Analysis. The results of this study concluded that the AIRQUAL indicator that became the priority order of improvement for the X airline is the cleanliness of the well-maintained aircraft toilets (Airline Tangible dimension), airline officials were willing to provide their assistance to everyone on the plane (personal service dimension), airline officers dressed well (empathy dimension) and ticket prices that are the same value as the service received (image dimension). Whereas Y Airline gets a positive CZSQ and d value. This indicates that Y Airline still outperforms X Airline in the attributes included in quadrant A in the CZIPA matrix. The AIRQUAL indicators that enter into the A quadrant are the availability of seats and the provision of promotions that are very attractive to passengers (image dimension) and clean and comfortable seats (Airline Tangible dimension). Keywords: Service Quality, airqual, importance-performance analysys (IPA) competitive zone of tolerance based on importance-performance analysys (CZIPA)